Ascertaining the Francophone population in Ontario: validating the language variable in health data - Batista, Ricardo; Hsu, Amy T.; Bouchard, Louise; Reaume, Michael; Rhodes, Emily; Sucha, Ewa; Guerin, Eva; Prud'homme, Denis; Manuel, Douglas G.; Tanuseputro, Peter (BMC Medical Research Methodology, 2024)
Abstract Background Language barriers can impact health care and outcomes. Valid and reliable language data is central to studying health inequalities in linguistic minorities. In Canada, language variables are available in administrative health databases; however, the validity of these variables has not been studied. This study assessed concordance between language variables from administrative health databases and language variables from the Canadian Community Health Survey (CCHS) to identify Francophones in Ontario.

Un centre communautaire pour la vie : un concept de « santé de la population » pour l’an 2000 - Couture, Roger T. (Reflets, 1999)
D’après les études épidémiologiques du Centre de santé publique du district de Sudbury (1992), il est important que cette communauté, comme maintes autres, s’attaque aux nombreux problèmes avec des idées nouvelles et des moyens plus efficaces pour améliorer la santé et contrôler l’évolution toujours plus onéreuse des coûts de santé. Depuis quelques années, nous savons que les stratégies de promotion de la santé peuvent aider les communautés de plusieurs façons. Pourtant, la promotion de la santé se situe loin dans la liste des priorités derrière le curatif ou les soins de première ligne dans le domaine de la santé. Ce texte vise à faire connaître comment on pourrait doter ce domaine d’une approche plus équilibrée en intégrant la dimension de la promotion de la santé. Pour ce faire, nous présenterons les objectifs d’une recherche, les approches et le processus que nous avons mené. Deuxièmement, nous ferons un survol des définitions et des modèles existants de la « santé de la population » (well being ou wellness) afin d’en dégager un modèle. Troisièmement, nous discuterons des obstacles à l’atteinte de la santé d’une population ou d’une communauté, notamment celle de la région de Sudbury. Finalement, nous proposerons un modèle communautaire de promotion de la santé qui fait le pont entre le modèle de santé de la population retenue et la communauté de Sudbury.

« Dialogue santé » une consultation historique auprès des communautés francophones de l’Ontario - Dallaire, Hélène; Rail, Geneviève (Reflets, 1995)

Initiatives intergénérationnelles en santé. Rapport final - Duguay, Benoît (La Commission nationale des parents francophones, la Fédération des aînées et aînés francophones du Canada et la Société Santé en français, 2007)
fs-ref-orig: Duguay, B. (2007). Initiatives intergénérationnelles en santé. Rapport final. La Commission nationale des parents francophones, la Fédération des aînées et aînés francophones du Canada et la Société Santé en français. fs-code-orig: Duguay-2007a

Le cours d’été en promotion de la santé, session 1999 - Fraser, Colette (1999)
Introduction: Depuis longtemps, on parle de l’importance de former les formatrices et les formateurs dans le domaine de la santé. Or, le Cours d’été en promotion de la santé (CÉPS) cherche justement à répondre à ce besoin depuis bientôt six ans dans la province de l’Ontario. Le ministère de la Santé de l’Ontario et le Centre for Health Promotion de l’Université de Toronto parrainent ce projet depuis ses débuts. Pourtant, l’étendue de cette expérience éducative dépasse largement le cadre et l’enceinte de l’institution universitaire. Cela s’est avéré particulièrement vrai lors de l’édition 1999 du cours d’été qui a lieu à l’Université Laurentienne de Sudbury du 31 mai au 3 juin. En plus d’avoir lieu dans le Nord de l’Ontario pour la première fois, ce cours d’été comportait trois volets culturels, soit les volets anglophone, francophone et autochtone. Conclusion: Le CÉPS continuera dans le nouveau millénaire à être un outil d’apprentissage pour ceux et celles qui s’intéressent à la promotion de la santé. Selon les évaluations des participantes et participants, il s’agit d’une activité à fortement recommander. Dans l’avenir, les individus choisiront la santé comme faisant partie intégrante de leur vie. Pour ceux et celles qui choisissent de le faire en français, il faudra veiller à constituer, dans le cadre du CÉPS, un volet francophone fort dans les années à venir. Pour nous en convaincre, rappelons en terminant les propos de Mauril Bélanger, secrétaire parlementaire de Patrimoine canadien, qui soulignait l’importance « de former des professionnels de la santé en français pour assurer à la population francophone des soins de santé dans sa langue »

Recrutement de prestataires de services maîtrisant le français : conseils et stratégies - Institut du savoir sur la santé mentale et les dépendances chez les enfants et les jeunes (2023)

Reach, adoption, and implementation strategies of a telehealth falls prevention program: perspectives from francophone communities across Canada. - O’Neil, Jennifer; Dionne, Nathalie; Marchand, Sylvie; Cardinal, Dominique; Handrigan, Grant; Savard, Jacinthe (Health Promotion and Practice, 2024)
Introduction. A fall may impact a person’s physical, emotional, and psychological well-being. Fall prevention programs are being implemented to reduce these negative outcomes. However, linguistic barriers in health services may reduce access to such prevention programs. A telehealth fall prevention program was designed to increase access to such programs in French for Francophone minority communities in Canada. This capacity-building project aimed to support community partners to deliver this telehealth program and document strategies used to reach, adopt, and implement the program within various Francophone and Acadian Minority Communities. Methods. A sequential explanatory mixed methodology was used to document reach, adoption, and implementation strategies and describe the lived experiences of program facilitators and organization representatives. Reach, adoption, and implementation were documented and analyzed descriptively, while lived experiences were analyzed using content analysis following the Consortium Framework for Implementation Research. Results. Twelve organization representatives or program facilitators from eight organizations operating in four different provinces participated in the study. Three themes emerged from the qualitative data on reach and adoption: external context, internal context, and capacity building. Four themes were identified as barriers and facilitators to implementation: level of preparation and time management, interpersonal relations and telepresence, exercise facilitation and safety, and technological problem-solving. Conclusion. Using tailored reach and adoption strategies such as prioritizing provinces with higher proportions of needs and training local community program facilitators may lead to the successful implementation of a new telehealth fall prevention program. Results from this study could potentially inform other primary prevention programs or telehealth program implementation.

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

An evaluation of FrancoForme: A case-managed home-based primary and secondary cardiovascular disease prevention program for French-speaking Canadians - Prince, Stephanie. A.; Laflamme, Marc; Harris, Jennifer; Tulloch, Heather E.; de Margerie, Michele (Journal of cardiopulmonary rehabilitation and prevention, 2017)
Purpose: Cardiovascular disease (CVD) is the leading cause of mortality globally. Telephone-delivered interventions targeting cardiovascular risk factors are gaining popularity. This study is an evaluation of FrancoForme, a cardiovascular risk factor reduction program for the primary and secondary prevention of CVD among French-speaking patients of Eastern Ontario. Methods: This study reports on changes in cardiovascular risk factors, weekly exercise levels, and psychosocial characteristics including anxiety, depression, and quality of life upon program completion (3 months) and at 1 year after the start of the program. Repeated-measures analysis of variance was used to compare changes in outcomes between primary prevention risk groups (low, moderate, and high risk for CVD) and the secondary prevention group (ie, cardiac rehabilitation) at baseline, 3 months and 12 months. Results: A total of 762 patients enrolled in FrancoForme between 2008 and 2015. At 3 months, all program completers (n = 507) experienced significant reductions for all cardiovascular risk factors except diastolic blood pressure. Minutes of self-reported exercise increased significantly by an average 90 minutes per week and all psychosocial variables improved. Significant group effects were observed across several risk factors. Among 12-month responders (n = 240), exercise, high-density lipoproteins, triglycerides, cholesterol, and all psychosocial variables were improved over baseline results. Conclusions: FrancoForme is unique in targeting both the primary and secondary prevention of CVD and removes several of the barriers to participating in a conventional CVD prevention program for French-speaking patients. FrancoForme is successful, receiving high satisfaction rates and resulting in significant improvements in cardiovascular risk factors, exercise, anxiety, and depression, as well as quality of life.

Évaluation de Marche vers le futur, un programme novateur de prévention des chutes offert par videoconference - Savard, Jacinthe; Labossière, Sophie; Cardinal, Dominique; Pinet, Bernard; Borris, Caroline (La Revue canadienne du vieillissement, 2018)
Several fall prevention programs have been implemented to reduce falls among seniors. In some rural areas or in French-speaking minority communities, the availability of such programs is limited. The objectives of this paper are to: (a) describe the Fall Prevention Program Marche vers le futur, offered in French, by videoconference; and (b) present the results of the evaluation of the program objectives. Results demonstrate that participants have improved their physical abilities, gained knowledge, adopted new behaviors and lifestyle habits. In short, Marche vers le futur reduces fall risk factors in a manner equal or superior to other programs. Marche vers le futur has made possible the provision of services in French in communities where availability of French-language resources is very limited, therefore fostering equity in access to health services.

L’impact d’un programme éducatif sur la qualité de vie de personnes aînées autonomes et hypertendues en milieu francophone minoritaire [thèse de maîtrise, Université d'Ottawa] - Taillon, Myriam (2016)
L’hypertension artérielle est une maladie chronique qui affecte près de 50 % des personnes de plus de 65 ans au Canada et de façon disproportionnelle, les communautés en situation minoritaire linguistique. L’objectif du projet était de sensibiliser des personnes de 65 ans et plus, hypertendues, en milieu francophone minoritaire aux facteurs de risque de l’hypertension par des ateliers éducatifs. L’impact de ces ateliers a été mesuré par un questionnaire sur la qualité de vie et des groupes de discussion. Il y a eu 34 participants. Les questionnaires ont révélé une amélioration dans les dimensions physique et mentale de la santé des participants (p < 0,001). Les groupes de discussion ont démontré que les participants comprenaient mieux la maladie et avaient modifié certains comportements. Les ateliers ont été reconnus comme très positifs par les participants. En conclusion, ce programme éducatif de 3 mois est efficace, faisable et apprécié chez cette population. Mots-clés hypertension artérielle, haute pression, francophone en situation linguistique minoritaire, personnes aînées, prise en charge, programme éducatif

Barriers to and enablers of attendance at diabetic retinopathy screening experienced by immigrants to Canada from multiple cultural and linguistic minority groups - van Allen, Zack; Dogba, Maman Joyce.; Brent, Michael. H.; Bach, Catherine; Grimshaw, Jeremy. M.; Ivers, Noah. M.; Wang, Xiaoqin.; McCleary, Nicola.; Asad, Sarah.; Chorghay, Zahraa.; Hakim, Hina; Sutakovic, Olivera; et al. (Diabetic medicine, 2020)
Aim To identify barriers to/enablers of attendance at eye screening among three groups of immigrantsto Canada from cultural/linguistic minority groups living with diabetes. Methods Using a patient-oriented research approach leveraging Diabetes Action Canada's patient engagement platform, we interviewed a purposeful sample of people with type 2 diabetes who had immigrated to Canada from: Pakistan (interviews in Urdu), China (interviews in Mandarin) and French-speaking African and Caribbean nations (interviews in French). We collected and analysed data based on the Theoretical Domains Framework covering key modifiable factors that may operate as barriers to or enablers of attending eye screening. We used directed content analysis to code barrier/enabler domains. Barriers/enablers were mapped to behaviour change techniques to inform future intervention development. Results We interviewed 39 people (13 per group). Many barriers/enablers were consistent across groups, including views about harms caused by screening itself, practical appointment issues including forgetting, screening costs, wait times and making/getting to an appointment, lack of awareness about retinopathy screening, language barriers, and family and clinical support. Group-specific barriers/enablers included a preference to return to one's country of birth for screening, the impact of winter, and preferences for alternative medicine. Conclusion Our results can inform linguistic and culturally competent interventions to support immigrants living with diabetes in attending eye screening to prevent avoidable blindness.